Preliminary survey of forensically important scuttle flies Diptera: Phoridae) in Universiti Kebangsaan Malaysia, Bangi - Shaz’wani Asyiqqin Shafe’i,; Raja Muhammad Zuha Raja Kamal Bashah, (Pusat Sistematik Serangga, Fakulti Sains dan Teknologi, Universiti Kebangsaan Malaysia, 2016)
Scuttle flies (Diptera: Phoridae) are diversified insect group of forensic importance with variety of habitats and feeding habits. Previous research showed diversity of scuttle flies associated with decomposing animal were abundant and their life cycles could likely be used as reference for minimum post mortem interval (PMImin) in forensic entomology. The objective of this research was to record and identify forensically importance scuttle fly species based on their sarcosaprophagous activity towards decomposed cow’s liver. Baited traps were placed at three selected locations in Universiti Kebangsaan Malaysia, Bangi, i.e. a secondary forest at Forensic Science Simulation Site, UKM lake and a pond for a period of 14 days. A total of 158 scuttle flies were collected (♀=153, ♂=5), representing 14 species and 7 genera. Dohrniphora cornuta (Bigot) was abundant at simulation site and pond while Megaselia scalaris (Loew) was the most frequent species found at the lake. A total of 42 specimens from genus Megaselia, Puliciphora, Spiniphora and Woodiphora could not be named until they are linked with their known males or females. These findings extend the information about the abundance and diversity of forensically important scuttle fly species in Malaysia.